Analisis Tradisi Larangan Pernikahan pada Bulan Kapit di Daerah Cirebon Perspektif ‘Urf - Shihah, Nila Yuwafa; Huda, M.Ikhwanul (JOM, 2024)
This study examines the prohibition of marriage during the month of Apit, corresponding to the Islamic month of Dzulqa'dah, which is a prevalent belief among the Javanese community, including in Jamblang Village, Cirebon Regency. The research aims to analyze the impact of this tradition on societal behavior and its implementation within the community. Employing a qualitative field research approach, the study utilized structured interviews with two respondents and document analysis to collect data. The research is descriptive in nature, focusing on presenting an in-depth understanding of the tradition. Findings reveal that the prohibition of marriage during the month of Apit, when analyzed from the perspective of Islamic jurisprudence ('urf), is categorized as 'urf fasid (a corrupt custom), as it instills a sense of fear among the community when performing marriages in this period. Theoretically, this research contributes to understanding the intersection of local traditions and Islamic legal principles, emphasizing the need to evaluate customary practices against Islamic jurisprudential frameworks.